A participação nas escolas: um currículo para as famílias? - Rosani Siqueira (2007)
In this dissertation, the functioning of discourse on the participation of families in two public schools belonging to Betim Public School District, Minas Gerais is studied. By means of empirical research conducted in two schools (in which two different texts that deal with the participation of the families in the school were collected, observations of the most different practices in family participation within the schools were made, and interviews of families and school employees were conducted), the different strategies used by each school are clearly shown in terms of how the participation works as well as how employees and family members are held co-responsible for solving school problems. The analysis was made by using some of the concepts taken from the work of Michel Foucault, such as power, government, and discourse. This study then discusses the manner in which family participation in the schools has been studied by Brazilian researchers, the type of participation material that circulates in the two researched schools (namely, advertising materials magazines, newspapers, invitations, and murals, instructional materials explanatory texts about the performance of programs like School Boards, Open Schools and Commissions; and institutional proclamations acts, decrees, and administrative rulings), events promoted by professionals from both schools with respect to the families, and what the professionals, students, and families of both researched schools think. The analysis of this material shows the power of the psychological and juridical discourses in the practice of participation, evinces how the affective techniques, responsible supervisors, and evaluators are essential to the performance of discourse in participation in the researched schools, and presents all of the divisions made by the participation and creation of a curriculum for the families, which is aimed at providing them with orientation as to how to take care of themselves, control their children, and actively participate in their scholastic lives. The general argument developed in the dissertation is that discourse on the participation of families in the researched schools is a government strategy to convince students parents or guardians of the importance of actively participating in the scholastic lives of their children. Moreover, this discourse also invests in the school professionals, mobilizing and encouraging them to demonstrate their commitment to education beyond the classroom.